(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Background. Intestinal parasitic infections remain a major public health concern, particularly in low-resource settings. They are associated with malnutrition, impaired growth, and developmental delays, especially in pediatric populations. Methods. A retrospective study analyzed 1,037 medical records from the Parasitology Clinic at Samarkand State Medical University, Uzbekistan, between December 2023 and March 2024. Data included age, sex, and laboratory-confirmed parasitic infections. Statistical analysis was conducted in Microsoft Excel 2010 using chi-square tests, with p < 0.05 considered significant. Results. The cohort (56.31% male, mean birth year 2017) revealed Giardia lamblia (24.42%) and Enterobius vermicularis (17.37%) as the most prevalent infections. Only one case of Entamoeba histolytica was identified. Giardiasis prevalence peaked in school-age children (30.79%) and adolescents (30.67%), while enterobiasis was most common in the elderly (38.46%). A significant sex-based difference in enterobiasis prevalence was observed (p=0.011), with higher rates among females. Conclusion. Intestinal parasitic infections remain an important health issue in Samarkand, predominantly affecting pediatric populations. Preventive measures, improved sanitation, school-based health programs, and continued epidemiological monitoring are essential to reduce the burden.